How is the Learning Achievement of Elementary School Students?-Breakfast and Study Concentration - Rachmat, Mochamad; Nur Fajri, Ashri (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: Learning Achievement is a benchmark of someone in achieving success in the academic field, one of the factors that influence it is the concentration of study and breakfast habits. Breakfast is useful to support learning concentration so that it can improve learning achievement. Learning Consentration affects learning achievement, one way to increase learning concentration is by having breakfast. Purpose: This study aims to analyze The Relationship of Breakfast and Study Concentration with Learning Achievement of Grade 5 Students at SD Negeri Pengasinan 03. Method: Analytical research with cross sectional design, the number samples was 57 students and taken by purposive sampling which fulfilled the inclusion and exclusion criteria. Method: Learning Achievement data obtained from the learning outcomes of even semester students. Breakfast data obtained using the food record method for 2 consecutive days, namely on weekends and weekdays. Study Concentration data obtained by the Digit Symbol Test method and using a stopwatch. Results: Data analysis with Chi-Square test. From 57 students, most of them have a breakfast frequency that is not routine (56,1%). High Study Concentration (64,9%) and Good Learning Achievement (80,7%). There is a significant relationship between breakfast and learning concentration (p-value = 0.008), there is no significant relationship between breakfast and learning achievement (p-value = 0.217), there is a significant relationship between learning concentration and learning achievement (p-value = 0.000).